2005
DOI: 10.1103/physrevlett.95.195501
|View full text |Cite
|
Sign up to set email alerts
|

A Universal Criterion for Plastic Yielding of Metallic Glasses with a(T/Tg)2/3Temperature Dependence

Abstract: Room temperature (T R ) elastic constants and compressive yield strengths of 30 metallic glasses reveal an average shear limit C 0:0267 0:0020, where Y C G is the maximum resolved shear stress at yielding, and G the shear modulus. The C values for individual glasses are correlated with t T R =T g , and C for a single glass follows the same correlation (vs t T=T g For a dislocation free crystal, Frenkel [1] calculated the theoretical shear strength by assuming cooperative shearing obtaining Y G=5. The yield s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

54
660
0
14

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,123 publications
(728 citation statements)
references
References 48 publications
54
660
0
14
Order By: Relevance
“…For small c, Du=R is proportional to ðH=RÞ 2 , consistent with the work of Conner et al [5]. Johnson and Samwer [23] found that at room temperature s c =m has the same value for most metallic glasses. From Eqs.…”
Section: Theoretical Analysis Of Shear-band Spacingsupporting
confidence: 77%
See 1 more Smart Citation
“…For small c, Du=R is proportional to ðH=RÞ 2 , consistent with the work of Conner et al [5]. Johnson and Samwer [23] found that at room temperature s c =m has the same value for most metallic glasses. From Eqs.…”
Section: Theoretical Analysis Of Shear-band Spacingsupporting
confidence: 77%
“…6a), and Du (Fig. 6b) 1)) that is relatively much more significant in MGs than in polycrystalline metals [23].…”
Section: Experimental Methodsmentioning
confidence: 99%
“…A 'potential energy landscape' (PEL) has been suggested for the glassy state [26][27][28][29]. Theories suggest the occurrence of a multi-stage state for atoms/molecules in a glass.…”
Section: Glasses and The Glass Transitionmentioning
confidence: 99%
“…Several models have been proposed to rationalize the inelastic deformation of MGs, which include free volume [6], shear transformation zone (STZ) [7][8][9], cooperative shear model (CSM) [10,11], flow unit [12], vibrational soft spot [13], shear-diffusive transformation [14,15], and our recently proposed tensile transformation zone (TTZ) [16][17][18]. All of these models are based on the local structural rearrangement of atoms via the interplay of atomic-scale shear and dilation/contraction in MGs [19][20][21][22][23][24].…”
mentioning
confidence: 99%